Fingolimod Does Not Reduce Infarction After Focal Cerebral Ischemia in Mice During Active or Inactive Circadian Phases. Issue 12 (12th October 2022) - Mandeville, Emiri T.; Li, Wenlu; Quinto-Alemany, David; Zhang, Fang; Esposito, Elga; Nakano, Takafumi; Mandeville, Joseph B.; Lee, Janice; Park, Ji Hyun; Arai, Ken; Waeber, Christian; Lizasoain, Ignacio; et al.
Abstract : Background: It has been reported that the S1P (sphingosine 1-phosphate) receptor modulator fingolimod reduces infarction in rodent models of stroke. Recent studies have suggested that circadian rhythms affect stroke and neuroprotection. Therefore, this study revisited the use of fingolimod in mouse focal cerebral ischemia to test the hypothesis that efficacy might depend on whether experiments were performed during the inactive sleep or active wake phases of the circadian cycle. Methods: Two different stroke models were implemented in male C57Bl/6 mice—transient middle cerebral artery occlusion and permanent distal middle cerebral artery occlusion. Occlusion occurred either during inactive or active circadian phases. Mice were treated with 1 mg/kg fingolimod at 30- or 60-minute postocclusion and 1 day later for permanent and transient middle cerebral artery occlusion, respectively. Infarct volume, brain swelling, hemorrhagic transformation, and behavioral outcome were assessed at 2 or 3 days poststroke. Three independent experiments were performed in 2 different laboratories. Results: Fingolimod decreased peripheral lymphocyte number in naive mice, as expected. However, it did not significantly affect infarct volume, brain swelling, hemorrhagic transformation, or behavioral outcome at 2 or 3 days after transient or permanent focal cerebral ischemia during inactive or active circadian phases of stroke onset. Conclusions: Outcomes were not improved by fingolimod in either transient or permanent focal cerebral ischemia during both active and inactive circadian phases. These negative findings suggest that further testing of fingolimod in clinical trials may not be warranted unless translational studies can identify factors associated with fingolimod's efficacy or lack thereof.